How Long Does Wolbachia Remain on Board?. (13th February 2017) - Bailly-Bechet, Marc; Martins-Simões, Patricia; Szöllősi, Gergely J.; Mialdea, Gladys; Sagot, Marie-France; Charlat, Sylvain
Abstract : Wolbachia bacteria infect about half of all arthropods, with diverse and extreme consequences ranging from sex-ratio distortion and mating incompatibilities to protection against viruses. These phenotypic effects, combined with efficient vertical transmission from mothers to offspring, satisfactorily explain the invasion dynamics of Wolbachia within species. However, beyond the species level, the lack of congruence between the host and symbiont phylogenetic trees indicates that Wolbachia horizontal transfers and extinctions do happen and underlie its global distribution. But how often do they occur? And has the Wolbachia pandemic reached its equilibrium? Here, we address these questions by inferring recent acquisition/loss events from the distribution of Wolbachia lineages across the mitochondrial DNA tree of 3, 600 arthropod specimens, spanning 1, 100 species from Tahiti and surrounding islands. We show that most events occurred within the last million years, but are likely attributable to individual level variation (e.g., imperfect maternal transmission) rather than population level variation (e.g., Wolbachia extinction). At the population level, we estimate that mitochondria typically accumulate 4.7% substitutions per site during an infected episode, and 7.1% substitutions per site during the uninfected phase. Using a Bayesian time calibration of the mitochondrial tree, these numbers translate into infected and uninfected phases of approximately 7 and 9 million years. Infected species thus lose Wolbachia slightly more often than uninfected species acquire it, supporting the view that its present incidence, estimated here slightly below 0.5, represents an epidemiological equilibrium.